2001
DOI: 10.1007/s007010170135
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Brain Tumours from Oesophageal Carcinoma: Neuro-Imaging and Clinicopathological Characteristics in Japanese Patients

Abstract: Among Japanese, the vast majority of primary esophageal cancers are squamous cell carcinomas. Therefore, MRI findings of a cystic tumour with a thin enhanced rim may alert one to the possibility of a metastatic brain tumour from the esophagus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 8 publications
1
20
1
Order By: Relevance
“…In those cases, BM was often misdiagnosed as meningitis, a pituitary tumor, or glioma. BM predominantly occurs after treatment [4,6,7,18,[20][21][22][23] based on the results of BM occurrence at 5 [27] , 6.7 [17] , 8.4 [28] , or 10 mo [29] after treatment, ranging from 4 to 57 mo. Clinical staging and adjuvant therapy are considered to be associated with BMEC, but the factors influencing the interval from treatment to BMEC occurrence have not been clarified.…”
Section: Misdiagnosis Of Bmec That Occurs Earlier Than the Diagnosis mentioning
confidence: 99%
See 1 more Smart Citation
“…In those cases, BM was often misdiagnosed as meningitis, a pituitary tumor, or glioma. BM predominantly occurs after treatment [4,6,7,18,[20][21][22][23] based on the results of BM occurrence at 5 [27] , 6.7 [17] , 8.4 [28] , or 10 mo [29] after treatment, ranging from 4 to 57 mo. Clinical staging and adjuvant therapy are considered to be associated with BMEC, but the factors influencing the interval from treatment to BMEC occurrence have not been clarified.…”
Section: Misdiagnosis Of Bmec That Occurs Earlier Than the Diagnosis mentioning
confidence: 99%
“…In recent decades, additional CT findings of BM have been reported. Among those reports, that by Takeshima and colleagues [28] of CT data from eight BMEC cases is considered as a classic report even today. Their study reported that CT displayed enhanced thin-walled cystic lesions in four of six squamous cell carcinoma cases and in both cases of small cell carcinoma.…”
Section: Uncertain Value Of the Unique Imaging Characteristics Of Bmmentioning
confidence: 99%
“…The survival periods once PTC is diagnosed with a BM as well as its individual treatments are presented in Table 3. Table 2 Average survival periods in months following specific treatment of brain metastases originating from thyroid carcinoma [16,17,23,[115][116][117][118] [32][33][34]. In the Western population, esophageal adenocarcinomas are more frequent.…”
Section: Survival and Outcomementioning
confidence: 99%
“…However, with the increased use of positron emission tomography (PET) at initial staging, along with advances in neuroimaging, the incidence of BM has gradually increased, as reported in the literature (6,7). Due to the rarity of BM in patients with EC, there is no standardized treatment for these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the rarity of BM in patients with EC, there is no standardized treatment for these patients. The survival time of patients with EC and metastasis to the brain ranges from 2 weeks to 25 months, depending on the extent of disease and the treatment modalities employed (7,8). Previously, it was demonstrated that patients with one to three BMs had improved survival rates with advanced treatment modalities (9).…”
Section: Introductionmentioning
confidence: 99%